Explaining voting participation gaps in local government elections in rural China. Issue 1 (March 2023) - Wu, Liyun; Rogers, Benjamin; Wang, Gang
When studying rural elections in China, scholars usually consider voting participation as consistent across the village and township levels. Using a cross-sectional research design based on data collected in 2009–2011 in rural China, this study reveals that voter turnout in village elections is significantly higher than in township elections. This finding is robust across regions and at different economic development levels. In addition, findings from multivariate regression analyses with bootstrapped Brier scores report that perceived fairness of elections and prevalence of low corruption are strong predictors for voter turnout. Gaps in voting participation of local government elections may reflect different political landscapes in rural governance in Chinese villages versus townships.